RESIN COMPOSITES DIRECT ODONTAL BULK FILL TECHNIQUE IN POSTERIOR TEETH - CASE REPORT - Iulian Băluţă; Irina-Maria Gheorghiu; Paula Perlea; Anca Nicoleta Temelcea; Sânziana Scărlătescu (Amaltea Medical Publishing House, 2019)
This article presents a modern technique in the field of direct dental restorations using composite resins. The wide variety of clinical situations we have encountered has forced the development of multiple modalities and materials to restore the loss of dental hard substance in the posterior areas. Among these, the bulk-fill technique, in which specific low-consistency composites are used, leads to a correct obturation in terms of marginal sealing, mechanical strength, and reduced risk of occurrence of postoperative sensitivity.